Financial Integration : A New Methodology and An Illustration - Rose, Andrew; Flood, Robert (Washington, D.C. : International Monetary Fund, 2004)
This paper develops a simple methodology to test for asset integration, and applies it within and between American stock markets. Our technique relies on estimating and comparing expected risk-free rates across assets. Expected risk-free rates are allowed to vary freely over time, constrained only by the fact that they must be equal across (risk-adjusted) assets in well integrated markets. Assets are allowed to have standard risk characteristics, and are constrained by a factor model of covariances over short time periods. We find that implied expected risk-free rates vary dramatically over time, unlike short interest rates. Further, internal integration in the S and P 500 market is never rejected and is generally not rejected in the NASDAQ. Integration between the NASDAQ and the S and P, however, is always rejected dramatically.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet